Chronic and recurrent benign lymphadenopathy without constitutional symptoms associated with human herpesvirus‐6B reactivation. (18th December 2015) - Forghieri, Fabio; Luppi, Mario; Barozzi, Patrizia; Riva, Giovanni; Morselli, Monica; Bigliardi, Sara; Quadrelli, Chiara; Vallerini, Daniela; Maccaferri, Monica; Coluccio, Valeria; Paolini, Ambra; Colaci, Elisabetta; et al.
Summary: Chronic/recurrent behaviour may be encountered in some distinct atypical or malignant lymphoproliferations, while recurrences are not generally observed in reactive/benign lymphadenopathies. We retrospectively analysed a consecutive series of 486 human immunodeficiency virus‐negative adults, who underwent lymphadenectomy. Neoplastic and benign/reactive histopathological pictures were documented in 299 (61·5%) and 187 (38·5%) cases, respectively. Of note, seven of the 111 (6·3%) patients with benign lymphadenopathy without well‐defined aetiology, showed chronic/recurrent behaviour, without constitutional symptoms. Enlarged lymph nodes were round in shape and hypoechoic, mimicking lymphoma. Reactive follicular hyperplasia and paracortical expansion were observed. Human herpesvirus (HHV)‐6B positive staining in follicular dendritic cells (FDCs) was documented in all seven patients. Serological, molecular and immunological examinations suggested HHV‐6B reactivation. Among the remaining 104 cases with reactive lymphoid hyperplasia in the absence of well‐known aetiology and without recurrences, positivity for HHV‐6B on FDCs was found in three cases, whereas in seven further patients, a scanty positivity was documented in rare, scattered cells in inter‐follicular regions. Immunohistochemistry for HHV‐6A and HHV‐6B was invariably negative on 134 lymph nodes, with either benign pictures with known aetiology or malignant lymphoproliferative disorders, tested as further controls. Future studies are warranted to investigate a potential association between HHV‐6B reactivation and chronic/recurrent benign lymphadenopathy.